On the order equivalence relation of binary association measures - Paradowski, Mariusz (Zielona Góra: Uniwersytet Zielonogórski)
Over a century of research has resulted in a set of more than a hundred binary association measures. Many of them share similar properties. An overview of binary association measures is presented, focused on their order equivalences. Association measures are grouped according to their relations. Transformations between these measures are shown, both formally and visually.
Keywords: association coefficient; result ranking; linear combination; zeroed variance determinant; feature selection